The Design and Comparison of Central and Distributed Light Sensored Smart LED Lighting Systems - Mehmet Ali Özçelik (International Journal of Photoenergy)
There is a lack of published peer-reviewed research comparing the efficiencies of distributed versus central sensor-controlled LED lighting systems. This research proposes improving the smart illumination of a room with external fenestration using central and distributed light sensors. The optical and electrical measurements of the daylight have been made in the case where the light was not distributed evenly and not sufficient. Test results show that the proposed distributed light sensor illumination system has increased the efficiency by 28% when compared to the proposed central system. It has also been shown that the two tested systems are more cost-effective than common smart illumination systems.